2020
DOI: 10.3390/jcdd7040059
|View full text |Cite
|
Sign up to set email alerts
|

Coconuts and Health: Different Chain Lengths of Saturated Fats Require Different Consideration

Abstract: The diet heart hypothesis has driven nutrition recommendations and policy for decades. Recent studies have questioned the hypothesis and sparked great controversy over the assumed connection between saturated fat intake and heart disease. Recent evidence suggests that dietary patterns should be the focus of dietary recommendations, not any one food or nutrient. Furthermore, to classify foods as simply saturated fat, polyunsaturated or monounsaturated fats is to ignore the many other potential nutrients and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 58 publications
1
23
0
3
Order By: Relevance
“…It has been reported in the literature that the main component conferring antibacterial properties to coconut oil is monolaurin, a heat-stable monoglyceride produced by the esterification of lauric acid and glycerol. Monolaurin appears to act primarily by destroying a variety of lipid-coated viruses by disrupting their membranes, thus interfering with assembly and maturation (Boateng et al, 2016;Hewlings, 2020). It is also attributed with the ability to permeate cell membranes by rendering the phospholipids of the lipid bilayer more fluid, inhibit membrane enzyme activities and nutrient uptake, and interfere with transduction signalling in bacteria (Khoramnia et al, 2013;Liebermann et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in the literature that the main component conferring antibacterial properties to coconut oil is monolaurin, a heat-stable monoglyceride produced by the esterification of lauric acid and glycerol. Monolaurin appears to act primarily by destroying a variety of lipid-coated viruses by disrupting their membranes, thus interfering with assembly and maturation (Boateng et al, 2016;Hewlings, 2020). It is also attributed with the ability to permeate cell membranes by rendering the phospholipids of the lipid bilayer more fluid, inhibit membrane enzyme activities and nutrient uptake, and interfere with transduction signalling in bacteria (Khoramnia et al, 2013;Liebermann et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Direct causal relationship between coconut fat and CVDs or CHD risk, is inconclusive as several studies even showed beneficial effect of coconut milk and coconut oil on lipid profile and CVD risk 59,60 . Thus, even though coconut contains primarily SFA, it is fundamental for the researcher to look at the length of SFA chain too, since different chain of SFA act differently metabolically and have different health effects 61 . These rather contradicting findings have led to inconclusive evidence, therefore further prospective longitudinal studies on coconut based foods, impacts of different types of SFA on health outcomes and CHD risk may be required to confim this association.…”
Section: Modelmentioning
confidence: 99%
“…long-chain triglycerides). Suma wszystkich kwasów nasyconych oleju kokosowego waha się między 90 a 95 % [21]. Nienasycone kwasy tłuszczowe (np.…”
Section: Charakterystyka I Pozyskiwanie Oleju Mctunclassified